2021
DOI: 10.3390/ijerph18041947
|View full text |Cite
|
Sign up to set email alerts
|

When Are Sexist Attitudes Risk Factors for Dating Aggression? The Role of Moral Disengagement in Spanish Adolescents

Abstract: This research aimed to explore the interplay of sexism and moral disengagement (MD) in the explanation of psychological and physical dating aggression. The sample comprised 1113 Spanish adolescents (49.2% girls, n = 552) between the ages of 12 to 17 (M = 14.44). A latent profile analysis conducted with sub-sample of 432 adolescents with sentimental experience identified four configurations: (1) benevolent; (2) less disengaged and sexist; (3) highly disengaged and sexist; and (4) moderately disengaged and sexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Compared with the non-violent adolescents, the other groups showed lower self-esteem and displayed a greater justification of violence against women and in conflict resolution. (for similar data, see Sánchez-Jiménez and Muñoz-Fernández, 2021).…”
mentioning
confidence: 57%
“…Compared with the non-violent adolescents, the other groups showed lower self-esteem and displayed a greater justification of violence against women and in conflict resolution. (for similar data, see Sánchez-Jiménez and Muñoz-Fernández, 2021).…”
mentioning
confidence: 57%
“…With regard to gender, we expected that boys considered public aggressions to be more frequent and less aggressive than girls (Lucero et al, 2014; Reed et al, 2017) (Hypothesis 4). Although no previous studies have been conducted on MD and cyber dating aggression associations, we expected to find significant associations following the studies conducted on face-to-face dating aggression (Rubio-Garay et al, 2019; Sánchez-Jiménez & Muñoz-Fernández, 2021). In other words, higher levels of MD will be related to a lower perception of aggressiveness (Hypothesis 5).…”
Section: Introductionmentioning
confidence: 93%
“…We hypothesized that: (H1) online jealousy would be a strong predictor of online control among boys and girls (Branson & March, 2021; Deans & Bhogal, 2019); (H2) moral disengagement would be a strong moderator between online jealousy and online control among boys and girls. Based on previous findings regarding the moderating role of moral disengagement in the association between sexism and dating aggression (Sánchez-Jiménez & Muñoz-Fernández, 2021) and the influence of this cognitive component on the perception of online control (Sánchez-Jiménez et al, 2021), we expected higher levels of moral disengagement to strengthen the relationship between online jealousy and online control. (H3) socio-emotional competence would moderate the association between online jealousy and online control.…”
Section: The Present Studymentioning
confidence: 99%
“…The extant scientific literature presents conclusive evidence regarding the strong association between moral disengagement mechanisms and bullying (Romera et al, 2019) and cyberbullying (Lo Cricchio et al, 2021). The association between this cognitive process and dating violence has been less explored, and the results point to a moderate relationship between these two variables (Maftei & Dănilă, 2021; Rubio-Garay et al, 2019; Sánchez-Jiménez & Muñoz-Fernández, 2021). A recent study (Sánchez-Jiménez et al, 2021) found that adolescents with high levels of moral disengagement perceived online control as less aggressive than their counterparts with low levels.…”
Section: The Contribution Of Moral Disengagement To the Understanding...mentioning
confidence: 99%